THE EFFECT OF INTENSITY USE OF SOCIAL MEDIA ON STUDENT ACADEMIC PROCRASTINATION - Amelia Dwi Astuti; Sentia Ariyanie (Program Studi PGSD Universitas Flores, 2023)
This study aims to determine the effect of the intensity of social media use on academic procrastination of Muhammadiyah University students of Palangkaraya. The research method used is quantitative. The population of this study was 2714, while the sample was 349 students. Data collection techniques were carried out by distributing questionnaires to students. Statistical testing using multiple linear regression analysis. The results of the study indicated that the significance value is 0.013 <0.05, so it can be concluded that there is a significant influence on the intensity of social media use on academic procrastination of Muhammadiyah University students of Palangkaraya.